2019
DOI: 10.1016/j.neubiorev.2019.01.021
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ANKK1 Taq1A and DRD2 C957T polymorphisms on executive function: A systematic review and meta-analysis

Abstract: Research in healthy adults suggests that C957T polymorphism of the dopamine D2 receptor encoding DRD2 and the Taq1A polymorphism of the neighbouring gene ankyrin repeat and kinase domain containing 1 (ANKK1) alter dopaminergic signalling and may influence prefrontally-mediated executive functions. A systematic review and meta-analysis was carried out on the evidence for the association of DRD2 C957T and ANKK1 Taq1A polymorphisms in performance on tasks relating to the three core domains of executive function: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 82 publications
(61 reference statements)
1
16
0
Order By: Relevance
“…Since the SNPs of MCT8, MCT10 and DIO2 are crucial for the function of thyroid hormones, we were interested if they would also influence cognitive functions and personality traits. There are numerous instances in which an influence of polymorphisms, mostly in monoaminergic genes, on both, cognitive processes [38][39][40][41] and personality traits [42][43][44][45] has been shown which motivated our approach. Previous studies have also shown that the amount of variance that can be explained by single polymorphisms is rather modest.…”
Section: Introductionmentioning
confidence: 99%
“…Since the SNPs of MCT8, MCT10 and DIO2 are crucial for the function of thyroid hormones, we were interested if they would also influence cognitive functions and personality traits. There are numerous instances in which an influence of polymorphisms, mostly in monoaminergic genes, on both, cognitive processes [38][39][40][41] and personality traits [42][43][44][45] has been shown which motivated our approach. Previous studies have also shown that the amount of variance that can be explained by single polymorphisms is rather modest.…”
Section: Introductionmentioning
confidence: 99%
“…In PD, impaired reuptake of dopamine due to presynaptic neuronal degeneration, or postsynaptic dopamine receptor stimulation by a dopamine agonist may lead to a loss of the normal physiologic response. [36] Dopamine receptor D2 which is involved in working memory, response inhibition and cognitive flexibility, mainly distributed in the striatum, [37] is a protein that is encoded by the DRD2 gene in humans. This gene encodes the D2 subtype of the dopamine receptor, which is coupled to the Gi subtype of the G protein coupled receptor that inhibits adenylate cyclase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding TaqIA, previous reports found that A1 allele carriers have been related to worse working memory performance [82][83][84], or with less cognitive flexibility [82,85,86]. However, after meta-analysis, the signification was lost [81]. C957T SNV's previous positive association with working memory function [87][88][89], and response inhibition [87,88,90] were also negative after a meta-analysis, while cognitive flexibility was still associated.…”
Section: The Functional Relationship Of Ankk1 and Drd2mentioning
confidence: 93%
“…The ANKK1/DRD2 locus has also been related to cognitive and emotional processes [73,80] that could be associated with risk for developing addictions. A recent systematic review and meta-analysis evaluated the association of ANKK1 TaqIA and DRD2 C957T SNVs in the performance of the executive functions in healthy adults [81]. Three main domains of executive functions were analyzed: response inhibition, cognitive flexibility and working memory.…”
Section: The Functional Relationship Of Ankk1 and Drd2mentioning
confidence: 99%
See 1 more Smart Citation